Compulsory treatment order and rehospitalisation: A New Zealand study. (June 2022) - Dey, Sangeeta; Mellsop, Graham; Obertova, Zuzana; Jenkins, Matthew
Objective: The effectiveness of compulsory treatment orders (CTO) in psychiatric practice is an area in need of evidence. There are no recent New Zealand publications on outcomes for patients under CTOs. This study examined the association between CTOs and subsequent rehospitalisation for patients with schizophrenia or related disorders. Method: Two year outcome data for 326 consecutive patients discharged in 2013 and 2014 was obtained from the Programme for the Integration of Mental Health Data database. Regression analyses were performed with rehospitalisation as the main outcome. Results: For the 54% of patients discharged under CTOs, rehospitalisation was 2–4 times more likely for the CTO group than for voluntary patients. Patients under CTOs also spent longer in hospital post index admission (IA). However, patients placed under CTOs during IA stayed longer than those under CTOs prior to IA. Ethnicity did not contribute significantly to any of the findings. Conclusion: This study did not show that patients under CTOs were associated with subsequent reduced resource use. The subgroup analysis suggested that studies with a longer follow-up period may provide better insight into the utility of CTOs.